Extension on the Brink - Meeting the Private Sector Challenge in the Information Marketplace - Michael D. Boehlje; David A. King (Journal of Applied Communications, 1998)
The Cooperative Extension Service is facing unprecedented competitive pressure in the information and education marketplace. As data are combined with knowledge to create information from which revenue and value can be gained, private information providers are placing Extension at a competitive disadvantage. As information customers reassess their needs and place higher value on convenience and access over objectivity, several questions must be answered. Chief among them: Can Extension and the Land-Grant System survive and succeed in head-to-head competition with private information providers, or will the system be most successful as a wholesale source of information and education in partnership with private-sector information providers?